PENGARUH FIRM SIZE, KEPEMILIKAN MANAJERIAL DAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Widyanata, Jhoda; Khuluqi, Khusnul (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The aim of this research is to analyze and empirically test the influence of firm size, managerial ownership and board of commissioners on corporate social responsibility disclosure. This research is a type of quantitative research using secondary data obtained from the Indonesian Stock Exchange and company websites. The population in this study was 125 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period using purposive sampling technique as the sample selection method, resulting in 33 companies that met the sample criteria. The data analysis technique used in this research is panel data regression analysis using Eviews 13. The results of this study reveal that partially the firm size variable has an influence on corporate social responsibility disclosure, while managerial ownership and the board of commissioners have no influence on corporate social responsibility disclosure.